Broken bridges—new school transitions for students with autism spectrum disorder: A systematic review on difficulties and strategies for success. (February 2019) - Nuske, Heather Joy; McGhee Hassrick, Elizabeth; Bronstein, Briana; Hauptman, Lindsay; Aponte, Courtney; Levato, Lynne; Stahmer, Aubyn; Mandell, David S; Mundy, Peter; Kasari, Connie; Smith, Tristram
Transitioning to a new school is often challenging for students with autism spectrum disorder. Few studies have examined the transition needs of students with autism spectrum disorder or the benefits of specific supports. This review synthesizes research findings on the difficulties that school transitions pose for students with autism spectrum disorder and their parents and teachers, and the strategies used to support students and parents during school transition. The review included 27 studies (10 examining the transition to primary school, 17 the transition to secondary school), with data from 443 students with autism spectrum disorder, 453 parents, and 546 teachers, across four continents (North America, Europe, Africa, and Australia). Studies reported that children with autism spectrum disorder struggled with anxiety and increased social pressure, their parents felt overwhelmed with complex placement decisions and worried about the well-being of their children, and teachers strove to provide appropriate supports to their students with autism spectrum disorder, often with inadequate resources. Findings indicated that the most useful strategies involved helping the student adjust to the new school setting, individualizing transition supports, clarifying the transition process for parents, and fostering communication both between the sending and receiving schools, and school and home.